Spatial analysis of disparities in basic household amenities in Haryana - Ritu Rani,; Pardeep Kumar Sharma,; Sandeep,; Rajesh Kumar,; Research Scholar, Department of Geography, Mahrishi Dayanand University Rohtak, Haryana., (National Geographical Journal of India, 2025)
Assessing the levels of socio-economic development has long been a significant focus for geographers. One of the key indicators of a region’s development status is the availability and quality of basic household amenities. These amenities serve as vital proxies for understanding the overall living standards and development conditions within a society or region. This study aims to examine rural–urban disparities in the availability of basic household amenities in Haryana, using selected indicators. Household-level data from the Census of India has been normalized, standardized, and spatially analyzed to reveal patterns of disparity across the state. The analysis, supported by appropriate statistical tools and mapping techniques, highlights a substantial gap between rural and urban areas in terms of access to essential household services. Based on the findings, the study proposes targeted measures to reduce this rural–urban divide. It advocates for immediate policy interventions aimed at ensuring equitable access to basic amenities through inclusive, group-specific approaches, complemented by awareness campaigns. To improve the overall quality of life and well-being of the rural population, the study emphasizes the need for development schemes